The Judas gate - Higgins, Jack (London : Harper, 2011)
A disturbing tape has made its way to British intelligence. It contains battlefield chatter from an ambush in Afghanistan, in which 12 U.S. Army Rangers and a British medical team died. Most of the Taliban voices are Afghan, but the voice of the commander bears an Irish accent. Sean Dillon is put in charge of hunting the traitor down.
Keywords: Intelligence officers -- Fiction; Suspense fiction